Analisis Efektivitas Iklan Destinasi Wisata Di Kabupaten Lahat - Karo Karo, Pelliyezer (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2024)
This research was carried out to evaluate video advertisements for the Ayik Pacar tourist destination in Lahat Regency, South Sumatra using the Customer Response Index (CRI) instrument with the AISAS (Attention, Interest, Search, Action, Share) concept. The research population is consumers who are reached while the tourist destination video advertisement is broadcast, with a sample size of 100 people. The research results show that all four models in the AISAS concept provide results with different CRI values. The four models studied include, the first AISAS model produces a CRI value of 21 percent, the second AIAS model produces a CRI value of 30 percent, the third AISS model produces a CRI value of 38 percent and the fourth AIS model produces the highest CRI value of 55 percent. An increase in the CRI value shows the best effectiveness of the advertising message in the fourth model. At the same time, the third model also shows quite good effectiveness, although it has not yet reached a value of more than 50 percent, but the CRI value is already greater than the No Search value for consumer responses. Apart from the CRI results, it is known that a new consumer response pattern has emerged, namely that consumers will not immediately plan to visit tourist destinations or even look for comparative information from the tourist destination they are going to.